Aspek Hukum dan Regulasi dalam Penggabungan Usaha (Merger dan Akuisisi) - Trio Ate, Yordanius; Nggala, Kanisius; Vivi Susanti, Agnes; Evarista E. Goma, Matilda; M. L. Sogen, Maria (Green Publisher Indonesia, 2025)
Mergers and acquisitions are a company's strategy to improve efficiency and competitiveness, but this process faces legal and regulatory challenges. In Indonesia, mergers and acquisitions are regulated in Law Number 40 of 2007 concerning Limited Liability Companies and Law Number 5 of 1999 concerning the Prohibition of Monopoly Practices and Unfair Business Competition. In addition, the Business Competition Supervisory Commission (ICC) is tasked with supervising mergers so as not to harm the market. This study uses a literature study method by examining regulations related to mergers and acquisitions, including financial accounting standards such as PSAK 103 and PSAK 38. Data is collected from legal journals, academic articles, and official regulatory documents. The results of the study show that mergers must be carried out in accordance with the law to avoid monopoly and unfair business competition. Law Number 40 of 2007 regulates the merger process, starting from shareholder approval to notification to creditors and employees. Law Number 5 of 1999 prohibits mergers that have the potential to create monopolies, and ICC has the authority to assess and cancel mergers that are detrimental to the market. In conclusion, merger and acquisition regulations in Indonesia are quite comprehensive, but the main challenge lies in the effectiveness of supervision by ICC and legal certainty for business actors. It is necessary to increase the implementation of regulations so that mergers are carried out fairly and in accordance with the law.